INTERREGIONAL ROUTES IN THE FORMATIVE PERIOD IN NORTHERN PERU AND SOUTHERN ECUADOR: A PERSPECTIVE FROM THE INGATAMBO SITE, HUANCABAMBA VALLEY - Yamamoto, Atsushi (2012)
This article presents a hypothesis about the interregional exchange routes during the Formative period in northern Peru and southern Ecuador from the point of view the Huancabamba Valley, especially the archaeological site of Ingatambo. This hypothesis is based on an analysis of GIS (Geographic Information Systems), «least-cost paths», and the comparison of archaeological materials. This analysis showed that the routes transformed gradually during the Middle Formative period due to a change in the transportation means, from traveling on foot to the use of camelids, which was closely related to the social change of the sites connected by them. Considering the excavated data of Ingatambo, there is a relationship between the selection of routes and the social context where interregional exchange and the establishment of contact with groups in neighboring areas become important as a social strategy.